ASPEK IMUNITAS DALAM PENANGANAN CORONA VIRUS DISEASE 2019 - Disantara, Fradhana Putra (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2020)
The Government of Indonesia has issued various regulations in an effort to provide a legal basis for the technical handling of COVID-19, including Presidential Decree (Keppres) No. 11 of 2020 concerning Stipulation of Public Health Emergency and President Regulation in Lieu of Law No. 1 of 2020 (Perppu) No. 1 of 2020 concerning State Financial Policy and Stability of the State Financial System for Handling Covid Pandemic 19 And / Or In Order To Face Threats That Harm National Economy And / Or Financial System Stability. With the Presidential Decree No. 11 of 2020, the Government of Indonesia establishes a public health emergency status. However, this raises problems, related to the proper legal status in the COVID-19 pandemic. In addition, the formulation of Article 27 of Perppu No. 1 of 2020 also left a problem, with Article 27 which actually provides a strong aspect of immunity for the implementers of the regulation. This type of research is legal research. This legal research aims to analyze the relevance of determining the state of public health emergency with the concept of an emergency state administration law, and identifying aspects of immunity in the formulation of Article 27 Perppu Number 1 of 2020. In this study a statute approach and conceptual approach are used, with an inventory of primary legal materials and secondary in order to get a proper analysis and critical analysis related to legal issues. The results showed that the proper legal status during the COVID-19 pandemic was state legal emergency, and the immunity aspect in the formulation of Article 27 of the Perppu contradicted with some Articles in the Constitution of the Republic of Indonesia 1945. So, The Constitutional Court must cancel the Article 27 of Perppu No. 1 of 2020